Innovation of sleeve packaging with holder using the implementation of augmented reality technology and braile system / Nur Farah Hanis Mohamad Johari ... [et al.] - Mohamad Johari, Nur Farah Hanis; Omar, Mastura; Rosnan, Shalida; Nordin, Nur Hanis; Ishak, Siti Nor Fatulhana (Universiti Teknologi MARA, Kedah, 2023)
Pulut Kuning was founded by Puan Zarina Zainuddin Dan Dato' Sri Abu Raihan. Starting of pulut kuning business in 2015 from a small kitchen to a Central Kitchen. Its successful break into Singapore and Brunei markets then make distribution to Petronas petrol stations across Selangor and Federal Territory. Pulut Kuning Zarina Zainuddin actual sleeve packaging has a few problem which is the product safety that required to be improve with a best way and method needed to produce a protection to this sleeve packaging. The problem statement is focusing on customer satisfaction which is there was a complaining because the packaging does not have holder because hard to hold also no protection on the product. The objective is to ease the customer to carry this product after purchased it from Mesra Petronas because there are no plastic bag provided. Pulut Kuning Zarina Zainuddin actual sleeve packaging doesn’t have a holder so the creative ideation of making a holder make it easier to hold so the product are able to grow out with the new invention with holder. Thus, the researcher also came out with the advanced technology innovation added which is Augmented Reality (AR). Not only that, the braille system also was introduced to the packaging which is to help blind or who have low vision to identify the product name on the packaging. This also can teach people to learn about Braille and further increase the widespread use of Braille system.